Displacement of Small bowel into the Lesser Sac in a Case of Complete Congenital Pouch Colon - Bilal Mirza; Muhammad Saleem (EL-Med-Pub, 2015)
Postoperative neonatal intestinal obstruction has a myriad of etiology. An operated case of imperforate anus developed intestinal obstruction early postoperatively. At re-operation, missed complete congenital pouch colon with a small perforation and displacement of small bowel into the lesser sac were found. The patient was managed by adhesionolysis, excision of pouch colon, and end ileostomy. The patient did well postoperatively.